Does access to care affect outcomes of appendicitis in children? - a population-based cohort study - To Teresa; Langer Jacob C (BMC, 2010)
Abstract Background The annual number of pediatric appendectomies in Ontario was stable throughout the study period, but with a significant level of regional variations across regions. The objective of this study is to use population-based data to measure the associations and to explain the variations of appendectomy rates with population socio-demographic indicators. Methods Appendectomy rates in children aged less than 19 years were calculated from Ontario hospital discharge data from 1993 to 2000. Small area variations in appendectomy and correlations between socio-demographic indicators were studied. Multiple logistic regression was used to measure the risk of negative appendectomy and perforation while adjusting for socio-demographic factors. Results The rate of positive primary appendectomy has been stable since 1993 with an average rate of 93.2 per 100,000 children. The negative appendectomy rates showed a significant decline over time from a high of 16.0 in 1994 to 10.2 per 100,000 in 2000 (p < 0.0001). There was a 4-fold regional variation in negative appendectomy with the highest rate of 26.0 per 100,000 in the northern regions of Ontario. After adjusting for socio-economic status, areas of higher percentages of rural living remained a single significant factor associated with a higher chance of negative and perforated appendectomy (OR = 1.28, 95% CI: 1.01, 1.61, p < 0.01 and OR = 1.11, 95% CI: 0.96, 1.28, p = 1.682 respectively). Areas with higher ultrasound use were associated with a lower risk of perforated appendectomy (OR = 0.83, 95% CI: 0.72, 0.95, p < 0.05). Conclusion The higher rates of negative and perforated appendectomy in rural populations underpin the influence of access to preventive and primary health care in modifying the odds of appendicitis resulting in surgery.